Prevalence of maxillary and mandibular physiological space in the primary dentition - Megan, Felisia Flaviana; Andiesta, Niekla Survia; Indriyanti, Ratna; Setiawan, Arlette Suzy Puspa Pertiwi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Physiological space is the space between maxillary and mandibular primary central incisors as well as maxillary and mandibular primary lateral incisors that occur during primary dentition period. The absence of physiological space will lead the crowded of permanent dentition due to discrepancy of the size of tooth and jaw. The objective of this study was to evaluate and analyse the prevalence of physiological space of maxillary and mandibular during primary dentition period. Methods: The type of research was a descriptive survey technique. The study was conducted at the Early Childhood Education (PAUD) in Bandung City throughout January-March 2017. The study population was children aged 3-5 years. Multistage cluster sampling used to choose subjects based on the division of the area from the city area to obtain the desired population. The data used were primary data obtained by examining the existence of a gap with a gap width indicator that is used as a benchmark of at least 0.5 mm with the help of WHO probe tool. Data were collected, processed and analysed using the SPSS (Statistical Package for Social Sciences) version 20. Results: A total of 65 out of 97 subjects had physiological space in their first dentition period. From 97 study subjects (100%) examined, 44 children (45.36%) had maxillary physiological space, and 53 children (54.64%) did not have maxillary physiological space. In 97 research subjects (100%) there were also 48 children (49.48%) having physiological space in the lower jaw, and 49 children (50.52%) did not have physiological space in the lower jaw. Conclusion: Prevalence of the maxillary and mandibular physiological space in the primary dentition period of children in the city of Bandung are 67.01%.